Fully-automated production of [68Ga]Ga-Trivehexin for clinical application and its biodistribution in healthy volunteers - Wang, Binchen; Jiang, Yaqun; Zhu, Jiaxu; Wu, Huiqin; Wu, Jianyuan; Li, Ling; Huang, Jianying; Xiao, Zhiwei; He, Yong (Frontiers in Oncology, 2024)
Background: The αvβ6-integrin targeting trimeric ligand [ 68 Ga]Ga-Trivehexin has emerged as a promising candidate for clinical application due to its clinical imaging potentials in various malignant cancers. Our objective was to develop a simplified and reproducible module-based automated synthesis protocol to expand its availability in clinical application.The pH value and the precursor load of radiolabeling were explored using an iQS-TS fullyautomated module. Radiochemical purity was evaluated by radio-HPLC and radio-TLC. The ethanol content, radionuclide purity and identity, bacterial endotoxins, sterility, and stability of the final product [ 68 Ga]Ga-Trivehexin were all tested. Biodistribution of [ 68 Ga]Ga-Trivehexin in healthy volunteers was also conducted.The synthesis was explored and established using fully-automated module with outstanding radiochemical purity (>99%). Considering molar activity and economic costs, a pH of 3.6 and precursor dose of 30 μg were determined to be optimal. All relevant quality control parameters were 2 tested and met the requirement of European Pharmacopoeia. In vitro stability test and imaging in healthy volunteer indicated the practical significance in clinical routines.A fully-automated synthesis protocol for [ 68 Ga]Ga-Trivehexin using the iQS-TS synthesis module was achieved and conformed to the clinical quality standards.Trial registration: ClinicalTrials.gov, NCT05835570. Registered 28 April 2023, https://www.clinicaltrials.gov/study/NCT05835570.